Kinetics and hydrodynamics of Candida antartica lipase-catalyzed synthesis of glycerol dioleate (GDO) in a continuous flow packed-bed millireactor. (1st November 2022) - Abd Razak, Nurul Nadiah; Cognet, Patrick; Pérès, Yolande; Gew, Lai Ti; Aroua, Mohamed Kheireddine
Abstract: Diacylglycerols (DAG) have been widely used in many industries due to their remarkable capabilities as emulsifiers and stabilisers. However, developing a sustainable and an effective synthesis method for DAG remains a challenge. Continuous flow bio-reactor is recognized to be more productive, controllable, and reliable instrument for developing green and intensified processes. In this work, a continuous ﬂow packed bed millireactor was employed for the synthesis of glycerol dioelate (GDO) catalyzed by immobilized lipase namely Candida antartica . Experiments were carried out to evaluate the kinetic parameters as well as to assess the internal and external mass transfer limitations. Using one-factor-at-a-time variables method, maximum oleic acid conversion and GDO selectivity were achieved at 85% and 74% respectively, at 0.15 g of lipase, 77 min of residence time with 1.6:1 molar ratio of oleic acid/glycerol. Hydrodynamic studies showed that the esterification reaction is kinetically controlled and unaffected by external and internal mass transfer. Employing Lilly–Hornby model for kinetic evaluation, K m values increased with increasing flow rates, whereas, V max appeared to be flow rate independent. Reusability tests revealed that the activity of immobilized lipase remained the same after 9 successive reaction cycles. At 11 days of operation, the stability of the lipase in the continuous packed bed millireactor decreased only 5–7%, indicating satisfying operational results and recyclability. This work may promote the enzymatic engineering synthesis of DAG, facilitating the creation of a cleaner and safer process. It has the potential to broaden the application of enzymes in continuous flow micro or millireactors.